2020
DOI: 10.5109/2558902
|View full text |Cite
|
Sign up to set email alerts
|

Primary Screening of German Chamomile Oil as Insecticides, Baits, and Fumigants in Nanoformulations against the Health Pest Periplaneta americana (L.) (Dictyoptera: Blattidae)

Abstract: Cockroaches are household pests with a health risk to humans. Natural products may have insecticidal activities against pest insects and thus inspire the development of novel insecticides as "biopesticides". In this study, we report a strategy to prepare nanoparticles of German chamomile (Matricaria chamomilla L.) oils (= essential oils or EO) to control the American cockroach in the two forms: one is coated with polyethylene glycol (PEG) as nanocapsiolation (NC) and the other is loaded with oil as a nanoemuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Previous studies established by many authors confirmed this findings, Abd El-Raheem & Eldafrawy (2016) and Said (2017) showed that the mortality percentages of the German cockroach nymphs and adults were increased by increasing the concentrations of the silver nanoparticles under feeding and contact methods. El-Khodary et al, (2020) Showed that the fumigation by the nanoemulsion of the German chamomile caused 44.44% mortality of P. americana at 10 mg/ liter after 72 h of application. Silva et al, (2019) reported that the encapsulated nanoparticles of the essential oils of (Piper aduncum L. and P. hispidinervum) caused about 80% mortality in Aedes aegypti.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies established by many authors confirmed this findings, Abd El-Raheem & Eldafrawy (2016) and Said (2017) showed that the mortality percentages of the German cockroach nymphs and adults were increased by increasing the concentrations of the silver nanoparticles under feeding and contact methods. El-Khodary et al, (2020) Showed that the fumigation by the nanoemulsion of the German chamomile caused 44.44% mortality of P. americana at 10 mg/ liter after 72 h of application. Silva et al, (2019) reported that the encapsulated nanoparticles of the essential oils of (Piper aduncum L. and P. hispidinervum) caused about 80% mortality in Aedes aegypti.…”
Section: Discussionmentioning
confidence: 99%